SISTEM INFORMASI PEMESANAN PAKET KUNJUNGAN WISATA BERBASIS WEB MENGGUNAKAN METODE WATERFALL DI DESA WISATA LEREP - Munasiroh Munasiroh; Abdul Rohman (Jurnal Mahasiswa Teknik Informatika, 2022)
Due to the negative impact of Covid-19 on various sectors, including the tourism sector, the government supports the implementation of regional travel for a tourism recovery, namely regional travel as an alternative form of tourism during the Covid-19 pandemic. And the Lerep Tourism Village as a rural tourism object needs to prepare several things to welcome the recovery of tourism, one of which is by providing information on online tour package options. In the development method, the researcher uses the waterfall method in building an information system for ordering tour packages in the Lerep Tourism Village. The waterfall method is a systematic or sequential method of developing applications and system software. Methods of data analysis using quantitative methods and testing methods using quantitative methods to obtain the final data. The results of this study, when viewed from the aspect of a system functionality, the black box method involved 1 examiner with a total of 50 test scenarios with the final results valid. and the usability test the percentage value is 81.6% from the visitor side, the percentage value is 86.85% from the manager side.Keywords: Tour Packages, Tourism Village, Waterfall, Covid-19